Five years of monitoring sooty bark disease (Cryptostroma corticale) on sycamore maple (Acer pseudoplatanus) in the floodplain forest of Leipzig, Germany - Georg Rieland; Rolf A Engelmann; Mathias Scholz; Demian Genau; Hans D Kasperidus; Christian Wirth; Jonas Till (PANGAEA, 2025)
As part of the "Lebendige Luppe" project, sooty bark disease was recorded on more than 1500 sycamore maples (Acer pseudoplatanus) (trunks >5cm breast hight diameter) on 60 plots (each 2500 m^2) in the late summers of 2020 to 2024. The selection of trees (according to their size) was based on 2 forest inventories (2016 and 2020) (Rieland et al. 2024, Scholz et al. 2022). As a result, new trees were added for recording in 2021. Tree damage caused by sooty bark disease was assessed via five damage classes according to the methodology outlined by Burgdorf and Straßer (2019). Trees that could not be found again were described as NA if there were no signs of felling.